An overview of power reactor kinetics and control in load-following operation modes - Žerovnik, Gašper; Čalič, Dušan; Gerkšič, Samo; Kromar, Marjan; Malec, Jan; Mihelčič, Anže; Trkov, Andrej; Snoj, Luka (Frontiers in Energy Research, 2023)
Previous work done on reactor kinetics and control in load-following operation modes available in open literature is reviewed. The analysis is focused on, however not limited to pressurized water reactors. Different approximations of the time-dependent neutron transport problem as well as different control algorithms are described in detail and compared. Due to lack of published information the majority of the comparisons was done on qualitative level. In order to facilitate future testing and intercomparisons of models and algorithms, two so-called reference scenarios with time-dependent power demand are defined: a scenario to test the limitations of the load-following capabilities of the nuclear facilities and a second, quasi-realistic scenario.